2008
DOI: 10.1007/s11060-008-9571-z
|View full text |Cite
|
Sign up to set email alerts
|

Atypical teratoid rhabdoid tumor (AT/RT) in adults: review of four cases

Abstract: Atypical teratoid/rhabdoid (AT/RT) tumor is a rare, highly malignant tumor of the central nervous system (CNS) most commonly found in children less than 5 years of age. Although the vast majority of cases are diagnosed in young children, there have been isolated case reports in adults. Since its histological appearance can be confused with other tumors, especially in adults, separating AT/RT from other neoplasms may be difficult. In many instances, a reliable diagnosis is not possible without demonstrating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 33 publications
3
52
0
Order By: Relevance
“…AT/RT was first recognized as a malignant intracranial rhabdoid tumor in an adult patient in 1992 by Horn et al 30 From then on, approximately 30 cases of adult AT/RT have been reported. [18][19][20][21][22][23][24][25][26][27][28][29][30] In contrast to the pediatric neoplasm, most adult CNS rhabdoid tumors are supratentorial, with only 3 tumors located in the cerebellum and 2 in the spinal cord. Most cases were diagnosed on the basis of characteristic histologic and immunohistochemical features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AT/RT was first recognized as a malignant intracranial rhabdoid tumor in an adult patient in 1992 by Horn et al 30 From then on, approximately 30 cases of adult AT/RT have been reported. [18][19][20][21][22][23][24][25][26][27][28][29][30] In contrast to the pediatric neoplasm, most adult CNS rhabdoid tumors are supratentorial, with only 3 tumors located in the cerebellum and 2 in the spinal cord. Most cases were diagnosed on the basis of characteristic histologic and immunohistochemical features.…”
Section: Discussionmentioning
confidence: 99%
“…This is a component of the SWItch/Sucrose Non-Fermentable chromatin remodeling complex and functions as a tumor suppressor by positively regulating transcription of a particular set of eukaryotic genes, possibly including the c-Myc target genes involved with differentiation and apoptosis. 19,22,24 The loss of expression of INI1 is considered to be diagnostic for AT/RT. 33 The diagnosis of AT/RT was not confirmed by cytogenetic or mRNA analysis, and this omission is a limitation of our retrospective review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,10,13,15,17,18 Only single cases have been reported in adults. [22][23][24][25][26][27][28][29][30][31][32] Several large, hospital-based series established an atypical teratoid/rhabdoid tumor prevalence of 1% to 2% among pediatric brain tumors, 8,[33][34][35] but population-based data on the incidence of atypical teratoid/rhabdoid tumors in children are not yet available. However, such data provide important insights into the burden of disease and might contribute to patient care.…”
mentioning
confidence: 99%